The Stability Characteristics of Sandbag Submerged Breakwater - Fatnanta, Ferry; Pratikto, Widi Agoes; Armono, Haryo Dwito; Citrosiswoyo, Wahyudi (UI Scholars Hub, 2010)
The Stability Characteristics of Sandbag Submerged Breakwater. Breakwater is one of coastal structures to overcome problems of abrasion. Due to difficulties in obtaining rock material at the coastal area. The using of sandbags as a breakwater provides advantages in utilizing local materials. A Sandbag has a smooth surface, so the internal shear forces are relatively small. According to these phenomena, the research for parameters that are expected to affect the stability of the sand bags. These parameters are a slope, shape and formation of sand bags. This experimental research conducted in two dimensional physical model and took place on the flume tank of Ocean Engineering Department, Faculty of Marine Technology, ITS. Scaled model 1 : 10. The bag was made in shapes, B1 and B2. Sand bags were prepared with the slope 1 : 1.5 and 1 : 2,0, width of top was 60 cm. The waves were regular waves, period of 1.5 seconds. The wave height was adjusted with the level of stability sand bags. It showed that the response of the sandbag was influenced by interlocking between sandbags. As a result, the stability depended on the change of wave forces, as a consequence of the change of slope and cross areas due to sandbags shape and formation type.